Optimizing MSME Financial Management to Increase Profits and Control Costs - Oktaviano, Benny; Triwibowo, Edi; Wulandari, Dian Sulistyorini; Saputra, Ilham Dwi (PT FORMOSA CENDEKIA GLOBAL, 2024)
This community service program aimed to enhance the financial management capabilities of Micro, Small, and Medium Enterprises (MSMEs) in the Tambun Selatan region. The program addressed common challenges faced by MSMEs, such as inadequate cost control, limited profit optimization strategies, and a lack of structured financial planning. Implemented over three months, the program involved interactive workshops, hands-on training, and follow-up consultations with [Insert Number] MSME participants from various sectors, including retail, food and beverages, and manufacturing. Key topics covered included cost classification, profit optimization strategies, budgeting techniques, and the adoption of financial tools. Results showed a significant improvement in participants' financial literacy, with average scores increasing by 45%. Additionally, participants reported an average 12% increase in profit margins and a 10% reduction in operational costs. Notably, 75% of participants adopted digital tools for financial tracking and management, marking a substantial shift in their operational practices. The program demonstrated that targeted financial training and localized solutions can significantly impact MSME profitability and sustainability.